1, 2, 3, 4-bis(p-methylbenzylidene sorbitol) accelerates crystallization and improves hole mobility of poly(3-hexylthiophene). (13th January 2016) - Yuan, Nana; Huo, Hong
Abstract: The addition of 1, 2, 3, 4-bis( p -methylbenzylidene sorbitol) (MDBS) does not change the nucleation mechanism or the crystal form of poly(3-hexylthiophene) (P3HT), but its presence increases the crystallization temperature ( T c ) of P3HT, decreases the crystallization half-time ( t 1/2 ) and accelerates P3HT crystallization, which indicates that MDBS is an effective nucleating agent for P3HT. An acceleration of P3HT crystallization by the addition of MDBS decreases the crystalline size and crystallinity of P3HT, and enhances the connectivity between ordered regions of P3HT, leading to the hole mobility rising from 1.99 × 10 –6 to 7.57 × 10 −5 cm 2 V −1 s −1 in P3HT:PCBM blend based hole-only devices with sandwich configurations. Our results suggest that accelerating P3HT crystallization by adding a nucleating agent might be an important factor to improve the hole mobility and balance the electron and hole mobility in a photovoltaic blend.